2013
DOI: 10.1186/scrt312
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the physiological barriers for successful mesenchymal stem cell transplantation into the central nervous system

Abstract: Over the past decade a lot of research has been performed towards the therapeutic use of mesenchymal stem cells (MSCs) in neurodegenerative and neuroinflammatory diseases. MSCs have shown to be beneficial in different preclinical studies of central nervous system (CNS) disorders due to their immunomodulatory properties and their capacity to secrete various growth factors. Nevertheless, most of the transplanted cells die within the first hours after transplantation and induce a neuroinflammatory response. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 145 publications
(167 reference statements)
2
26
0
Order By: Relevance
“…Previous studies have proposed that reactive astrocytes form scar-like barriers surrounding the grafted MSCs, which sequesters them from immune effector cells, or that astrocytes infiltrating the graft may provide cellular and structural support for graft survival (Coyne et al 2006;De Vocht et al 2013a;De Vocht et al 2013b;Praet et al 2012). Our data demonstrated the induction of VEGFR-3 protein, but not its ligand, in reactive astrocytes at the graft site.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Previous studies have proposed that reactive astrocytes form scar-like barriers surrounding the grafted MSCs, which sequesters them from immune effector cells, or that astrocytes infiltrating the graft may provide cellular and structural support for graft survival (Coyne et al 2006;De Vocht et al 2013a;De Vocht et al 2013b;Praet et al 2012). Our data demonstrated the induction of VEGFR-3 protein, but not its ligand, in reactive astrocytes at the graft site.…”
Section: Discussionsupporting
confidence: 56%
“…Altogether, it is likely that the neuroinflammatory response in engrafted brain tissue is not induced by MSCs secreting VEGF-C but is rather a phenomenon secondary to cell death observed after allogeneic or xenogeneic stem cell transplantation into the CNS (De Vocht et al 2013a). Previous studies have suggested that even autologous MSC grafts as well as allo-or xenogeneic stem cell grafts in the rat brain can trigger robust microglial activation and severe astrogliosis (Camp et al 2009;Tambuyzer et al 2009;Bergwerf et al 2011;De Vocht et al 2013a;De Vocht et al 2013b). In addition, Khoo et al (2011) reported that the glial reaction after transplantation of human MSCs into the rat brain occurs in the presence of cyclosporine immunosuppression, indicating that it is not specific to the transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to insufficient GFP expression and the complexity and cost of development of transgenic animals, vector-mediating GFP transfection in vitro is still the preferred technique for GFP labeling. [166][167][168] The generation of various colors of blue/yellow-shifted GFP variants, or the mutation-based development of red fluorescent proteins from …”
Section: Reporter Genes Fluorescent Proteinsmentioning
confidence: 99%